ESG, CEO Tenure, and Firm Performance: A Real Estate Dilemma in ASEAN-6 - Doni Iwan Prasetyo; Y. Anni Aryani (Jurnal Akuntansi dan Keuangan, 2025)
This study examines the effect of ESG (Environmental, Social, and Governance) disclosure on the performance of real estate companies in the ASEAN-6 region, with CEO tenure as a moderating variable. Using panel data from 2016 to 2023, covering 424 observations of real estate firms listed on ASEAN-6 stock exchanges, this study employs the Random Effect Model (REM) to analyze the relationships between variables. The findings reveal that ESG disclosure has a negative and significant impact on firm performance, as measured by Tobin's Q. However, the interaction between ESG disclosure and CEO tenure exhibits a positive and significant effect. These results indicate that longer-tenured CEOs can moderate the relation-ship between ESG disclosure and firm performance. The implications of this research provide valuable insights for companies to enhance ESG transparency and consider leadership stability in optimizing long-term performance.